Pendekatan Konseling Psikoanalisis: Kajian Literatur tentang Konsep, Teknik dan Relevansinya dalam Praktik Konseling - Florent Ema Weking; Rusmanita Amalia Sari; Budi Purwoko; Bakhrudin All Habsy (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2026)
This article discusses counseling approaches and theories, with a primary focus on the psychoanalytic counseling theory. Psychoanalytic theory, developed by Sigmund Freud, emphasizes the importance of the unconscious mind, past experiences, and intrapsychic dynamics in shaping individual behavior and personality. This article outlines the fundamental concepts of psychoanalysis, such as the structure of personality (id, ego, superego), defense mechanisms, and counseling techniques used, including free association, dream interpretation, and transference. In addition, this article also examines the strengths and limitations of the psychoanalytic approach in modern counseling practice. Through a narrative literature review with the stages of identification, selection, classification, and content analysis of relevant sources, this article aims to provide a comprehensive understanding of the relevance and application of psychoanalytic theory in helping individuals overcome psychological problems. It is expected that this article can serve as a reference for practitioners, academics, and students in developing insights into the theory and practice of psychoanalytic counseling.